Enhancing Family Resilience for Religious Moderation: Preventing Radicalism through Digital Religious Literacy - Ilman Nafia; Slamet Firdaus; Septi Gumiandari (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2024)
This article discusses the importance of the family's role in preventing religious radicalism and promoting religious moderation through digital religious literacy. The research aims to explore the level of family digital literacy among Muslims in Cirebon and its role in strengthening family resilience as a key element in addressing potential radical challenges. Using a mixed-methods approach with questionnaire surveys and interviews, the study reveals that religious conflicts in Indonesia, particularly in Cirebon, stem from factors like low religious literacy among millennials, driven by a lack of interest in reading and a limited understanding of religious teachings. Technology and social media exacerbate these conflicts, involving violations of religious freedom, intolerance, and blasphemy, persisting despite regulations and threatening multicultural harmony. Family resilience, encompassing economic, psychosocial, and socio-cultural aspects, plays a crucial role in countering religious radicalism. As the smallest social institution, the family transmits values, with economic resilience preventing the infiltration of radical ideas. Empowering families as moderation agents is vital, and strategies for enhancing family digital literacy, including education and awareness campaigns, monitoring online activities, promoting quality information sources, developing critical thinking skills, and using content filters, contribute to building resilience against radical influences. The study's results are expected to enrich academic literature by applying the concept of family resilience, specifically in preventing radicalism and promoting religious moderation. The findings strive for a direct impact on practical efforts to prevent radicalism, contributing to the formation of an inclusive and moderate society.Keywords: Family Resilience, Digital Religious Literacy, Religious Moderation